"LIGHT" AND "SHADOW" OF A.S. MAKARENKO'S PEDAGOGICAL TRADITION - D Klus-Stanska; A. A. Polonnikov (Moscow Polytechnic University, 2017)
The issue discussed in the article concerns the attitude to the heritage of the Soviet pedagogue A.S. Makarenko. The paper states the idea of inaccessibility of this heritage to direct perception, which determines the reception of Makarenko's experience as an issue of reading and interpretation. There are described three reconstructive strategies of this tradition, as well as the repercussions of their implementation for the current education and culture. The authors discover the connection of the reconstruction strategies with ideology, the authorities' relationships, and the political project approved with the help of the strategies' mediation.